Pengaruh Perbedaan Jenis Umpan Segar Terhadap Hasil Tangkapan Kepiting Bakau (Scylla Serrata) Pada Alat Tangkap Bubu Lipat Di Lingkungan PerairanMangrove Kecamatan Panimbang, Banten - Muhammad Syahdan Haqi; M. Tajuddin Noor; Gilang Rusrita Aida; Achmad Kusaeri (Jurnal Perikanan Unram, 2024)
The increasing demand for mangrove crab production requires effective innovation to increase mangrove crab production. One of the efforts made to increase mangrove crab production is by conducting operational activities to catch mangrove crabs using folding traps and effective bait, because the success of the catch depends on the bait. The objective of this study was to determine how different types of fresh bait affect mangrove crab catches and to determine the most optimal fresh bait for mangrove crab catches. This study was conducted using a randomized block design (RCD) consisting of three treatments and nine trips. The results showed that the highest average catch was in fresh pepetek fish bait (treatment A) with an average value of 4.33, and the lowest average catch was fresh chicken offal bait (treatment C) with an average catch value of 1.00. Based on the results of the Anova test, the results show that the comparison of the P value is 0.000 <0.05, so H0 is rejected and Hi is accepted, meaning mangrove crab catches were strongly influenced by the different types of fresh bait used, followed by the Duncan test which shows that different notations are obtained from all treatments, where no treatment is located in one subset, meaning that between treatments do not have the same results or each treatment has a difference number of catches. In treatment C using fresh chicken offal bait obtained the lowest mean catch and the highest treatment A when compared to treatments A and B. The order of the average mangrove crab catches from lowest to highest occurred in treatments C, B and A